Frequency and Histopathological Characteristics of Malignant Tumors Reported at Tertiary Care Hospital - Saima Gulzar, Huma Khaliq, Noor Us Sabah Ahmed, Sobia Anwar, Iram Kehkashan Khurshid, Navid Qureshi, Muhammad Zeeshan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cancer is a very important cause of worldwide mortality, and therefore, a continuous updated research is always needed regarding types of cancers in a particular area, histopathological grades and prevalence of cancer .Only a limited research work is available in our country in the field of cancer and histopathology. Objective: To express the prevalence of cancers and types of carcinoma with age, gender, site, and histopathological type, histopathological grades. Study Design: Descriptive study Place and Duration of Study: Department of Pathology, Pak Red Crescent Medical & Dental College, Dina Nath from 1st July 2018 to 30th June 2023. Methodology: One hundred and ninety four male and female patients were enrolled. Patients >12 years and with malignancy were included. Results: The average age of patients was 51 years and most of the patients were females. Predominant cancers were of breast and cervix. Around 88% of patients had carcinoma, of which mostly were females. Sarcoma was also more common in females whereas lymphoma was seen mainly in male patients .(P<0.05) also shows the maximum percentage of female had cancer as compared to male patients. The highest percentage of patient of carcinoma and sarcoma were of grade-2 and Lymphoma seen was of high grade. Conclusion: Most of the findings in prevalence and cancer subtypes were similar to other studies in Pakistan with a few differences, which are due to difference in facilities provided. Most patients had advanced grades of cancer, when prognosis is no longer favourable. Keywords: Cancer, Prevalence, Breast cancer, Stage, Grade, Histopathology